INVESTIGASI KOMPONEN GREEN MARKETING TERHADAP GREEN PURCHASE INTENTION PRODUK UKM JAWA TIMUR: (STUDI PADA KONSUMEN GREEN PRODUCT UKM KHAS JAWA TIMUR) - Anita Astini Hidayah; Sri Setyo Iriani; Yessy Artanti (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
Plastic waste is now a concern for the people, especially Indonesia, which is known to be dangerous because it is difficult to decompose and cannot be recycled. The biggest source of plastic waste comes from household activities and the food and beverage industry. Therefore, business actors are required to change all business activities to be environmentally friendly. One of them is the East Java UKM business actors who have the characteristics of food/snacks in each region. The purpose of this study was to analyze the influence of the components of green marketing, namely green brand knowledge, environmental knowledge, attitudes towards green purchase intention on typical East Java UKM brands/products. The research method used is a quantitative approach by distributing questionnaires through social media to 100 respondents. The criteria for the respondents were consumers who had purchased typical East Java UKM products, one of which was pudak, jubung, getuk banana, madu mongso and jumbrek, ranging in age from 18-55 years. The data analysis method uses multiple linear regression and was processed using the SPSS 16 program. The results of the study show that green brand knowledge and attitudes have a significant effect on green purchase intention. Meanwhile, environmental knowledge has no effect on green purchase intention. Keywords: GBK, EK, Attitude, GPI